EVALUATION OF INSECT INFESTATION AND BACTERIAL LOAD IN SMOKE-DRIED Clarias gariepinus IN WASE, PLATEAU - NIGERIA - Yusuf, Zikrullah; Abdulkarim , Mohammed (Nigerian Journal of Fisheries, 2025)
Evaluation of insect infestation and bacterial load in smoked-dried Clarias gariepinus was carried out to determine insect pest and bacterial contaminants in Wase, Bashar and Kampani Zurak markets which constituted a dietary intake of inhabitants of Wase, Plateau State, Nigeria. Ninety smoked-dried Clarias gariepinus (1500g) were bought from the markets. Dermestes maculatus had 1666 (96%), Necrobia rufipes, 59 (3%) and Ahasverus advena: 9 (1%). Insect pest populations of their developmental stages show that larvae had the highest: 1584 (91%) with pupae least, 9 (1%). Bashar had highest 263 (15%) insect: Kampani zurak: 1098 (63%) and lowest in Wase: 82 (91.1%). There was significance difference (P < 0.05) between insect populations in smoked-dried C. gariepinus in the markets. Bacterial load in fish samples was determined using pour plate method and characterization of various isolates were based on biochemical tests. Mean bacteria count in smoked- dried C. gariepinus revealed that Wase had the highest: 5.01x106cfu/g while Bashar was lowest: 1.41x107cfu/g. Bacteria species isolated revealed that Staphylococcus spp had the highest 48(58%) while Bacillus species was lowest: 4(5%). Retailed smoked, dried Clarias gariepinus were highly infected with the insect Dermestes maculatus and Staphylococcus spp. Clarias gariepinus obtained from fishers should be properly preserved.